Persepsi Keparahan dan Manajemen Glukosa Mandiri pada Pasien Diabetes Mellitus Tipe 2 - Hasri, Shania Nursiah; Oktamianti, Puput; Candi, Cicilya; Kurtanty, Dien (FORIKES, 2024)
Routine self-management of glucose is a crucial aspect for people with type 2 diabetes mellitus which is related to preventing complications as a form of diabetes management at home. Patients need unwavering confidence in their ability to consistently control the disease. Therefore, this study aimed to examine the relationship between perceived severity as part of one's beliefs and glucose self-management in patients with type 2 diabetes mellitus. This research was a quantitative study with a cross-sectional design. This study involved 274